Gerakan Kampanye Stop Bullying: Pencegahan dan Penanganan Bullying di MAN 1 Maluku Tengah - Mahaly, Sawal; Ellis, Rusnawati; Lating, Ainun Diana; Asrul, Asrul; Jumail, Jumail; Galib, Izatul Janah; Nurmin, Nurmin (-, 2025)
Bullying is a serious problem in schools as it affects mental health, learning motivation, and the educational climate. This phenomenon often occurs in physical, verbal, or psychological forms, and if left unaddressed, it can hinder students’ development. Therefore, concrete steps are needed to raise students’ understanding and awareness in preventing and handling bullying. This study aims to improve students’ understanding, awareness, and commitment to bullying prevention through the Stop Bullying Campaign at MAN 1 Central Maluku. The method included socialization, group discussions, and educational games, with evaluation using pre-test and post-test on 65 tenth-grade students. The results indicated significant improvements: understanding of bullying definitions increased from 43% to 92%, awareness of bullying types from 38% to 89%, awareness of its impacts from 46% to 94%, knowledge of reporting procedures from 34% to 88%, and prevention commitment from 54% to 97%. These findings confirm the effectiveness of the campaign in creating a safe, supportive, and bullying-free school environment.